Increased repeat syphilis among HIV-infected patients: A nationwide population-based cohort study in Taiwan. Issue 28 (10th July 2020) - Lee, Nan-Yao; Chen, Yen-Chin; Liu, Hsiao-Ying; Li, Chung-Yi; Li, Chia-Wen; Ko, Wen-Chien; Ko, Nai-Ying
Abstract : Abstract: Among human immunodeficiency virus (HIV)–infected individuals, syphilis is an important sexually transmitted infection (STI), and repeat infections are common. Identifying risk factors for delineating the trends in repeat syphilis are essential for STI and HIV prevention. This study is to investigate the dynamic of the syphilis epidemic among HIV-infected patients and to identify the risk factors associated with repeat syphilis. A population-based cohort design was used to analyze claim data between January 2000 and December 2010 using the Taiwan National Health Insurance Research Database. The Poisson regression test was used to identify risk factors for repeat syphilis. Of 13, 239 HIV-infected patients, annual syphilis screen tests have been performed in 4, 907 (37.1%) of these patients. Syphilis has been diagnosed in 956 (19.5%) patients, and 524 (10.7%) had repeat syphilis. The annual trend in repeat syphilis showed a significant increase in the study period ( β  = 0.23, P  < .001). Younger age (adjusted incidence rate ratio [aIRR] 1.43; 95% CI 1.11–1.86), male gender (aIRR 11.14, 95% CI 4.16–29.79), a history of STIs (aIRR 1.39, 95% CI 1.21–1.59) were independently associated with repeat syphilis. The retention in HIV care and adherence to antiretroviral therapy ≥85% ([aIRR] 0.77, 95% CI 0.61–0.98; P  < .001) were associated with a reduced risk of repeat syphilis. The incidence of repeat syphilis increased during 11 years of follow-up. The screening of syphilis for early diagnosis and retention in HIV care with medication adherence should be encouraged to minimize the risk of repeat syphilis in the targeted population.